SV-regeringens forudsætninger og forløb - Borchsenius, Søren (Historisk Tidsskrift, 2013)
The Social Democratic-Liberal Government’s Background, Formation and Short Life In the summer of 1978 the Danish Social Democratic party and the Liberal Party formed a coalition government. Its main purpose, it claimed, was to restore Denmark’s economy, which had deteriorated steadily since the first oil crisis. The government was an ’historic’ experiment, because the two parties had a long record of opposition to each other. This article deals with the government’s formation, its course and the reasons why it lasted little more than one year. In August 1978, when the two parties decided to form a coalition government, both parties had an interest in restoring the economic situation, though other motives concerning the parliamentarian situation, the parties’ interests, and personal motives also played a role. The most important agreement between the two parties was a declaration of intent concerning incomes policy. The aim was a tight incomes policy in the years to come. The government planned tripartite negotiations between trade unions, employers and government. The trade unions strongly resented the coalition. Prime Minister Anker Jørgensen, leader of the Social Democratic party, was heavily influenced by the confrontations between the party and the trade unions. Instead of fighting for the coalition, Anker Jørgensen sought to satisfy the trade unions. The government did not succeed with the tripartite negotiations. In the end the government had to make another statutory incomes policy solution. It was a solution that did not fulfil the declaration of intent concerning incomes policy, but it was a solution that pleased the trade unions. In September 1979 the government broke down, only partly because of internal disagreement about policies to fight the economic crisis, but mainly due to the Social Democrats’ unclear position. The party’s weak leader had limited priorities concerning the economy and too many internal problems.